Gümüşhâneli Dergâhı Şeyhlerinden Safranbolulu İsmail Necati: Hayatı, Halifeleri ve Eseri / Safranboluian Ismail Najati, One of the Sheikhs of Gumushkhanawi Lodge: His Life, Khalifas and Work - Yılmaz, Necdet (Journal of History Culture and Art Research, 2019)
Abstract Ismail Najati efendy was born in Safranbolu in 1258/1842-3. After completing primary education in his hometown, he came to Istanbul and completed his education there, then he was engaged in teaching as a mudarris. Besides being a participant of Huzur Lessons as a muqarrir and mukhatap, he taught as a professor in the madrasa of Dar al-khilafat al-aliyye. His relationship with Ahmad Ziyaaddin Gumushkhanawi, the scholar-sufi of that era, began in his pupilage and continued in the form of professor-student and sheikh-disciple relation until the death of Gumushkhanawi. He attended the lessons of Gumushkhanawi, took scholarship ijazats and also khilaftnamah from him by completing his sayr al-suluk. He undertook the sheikhdom of Gumushkhanawi Lodge, which was the grand lodge of Ziyaiyyah sûfî order attributed to Gumushkhanawian Ahmad Ziyaaddin Efendy, succeeding Kastamonuian Hasan Hilmy Efendy and conducted this mission until his death. As a mudarris and a sheikh he gave ijazats to numerous students regarding hadith books that he taught. He also gave khilafatnamah to his merited disciples who were taken by himself to khalwats/seclusions, one of the rutin activities of the Lodge. As far as we identified, the number of his khalifas was twenty five. His pamphlet titled Sayr al-Suluk Lessons and postscript to the book of Ramuz al-ahadith are written works of him. In this paper, by presenting the life, scholarly career, lodge activities and khalifas of Ismail Najati Efendy, and briefly examining his pamphlet regarding sayr al-suluk, we sought to introduce this outstanding scholar and wise man. Öz İsmail Necati Efendi, 1258/1842-3 senesinde Safranbolu’da doğmuş, ilk tahsilini memleketinde tamamladıktan sonra İstanbul’a gelerek burada tahsilini tamamlamış, ardından da tedris faaliyetlerinde bulunmuş bir müderristir. Huzur Dersleri mukarrir ve muhataplığı yanında Dârü’l-hilâfeti’l-aliyye medresesi hocalığı da yapmıştır. Dönemin alim sûfîlerinden Ahmed Ziyâeddîn-i Gümüşhânevî ile daha talebeliği döneminde başlayan münasebeti hoca-talebe ve şeyh-mürid ilişkisi şeklinde onun vefatına kadar devam etmiştir. Gümüşhânevî’nin derslerine katılarak hem ilim icâzetleri hem de seyr ü sülûkünü tamamlayarak hilâfetnâme almıştır. Gümüşhaneli Ahmed Ziyaeddin Efendi’ye nispet edilen Ziyâiyye tasavvuf yolunun âsitânesi olan Gümüşhânevî dergâhının Kastamonulu Hasan Hilmi Efendi’den sonra şeyhliğini üstlenerek vefatına kadar bu vazifeyi yürütmüştür. Pek çok talebeye hem bir müderris olarak hem de dergâhın şeyhi olarak okuttuğu hadis eserlerine dair icâzetler vermiştir. Dergâhın rutin faaliyetlerinden olan halvetlere aldığı kimselerden liyâkat kesbedenlere de hilâfetnâme vermiştir. Tespit edebildiğimiz kadarıyla yirmiş beş kişi halifesi olmuştur. Seyr ü Sülûk Dersleri adlı risâlesi ile Râmûzü’l-ehâdîs kitabına yaptığı hâşiye yazılı çalışmalarından olan İsmail Necati Efendi’nin hayatı, ilmî kariyeri, dergâh faaliyetleri ve halifeleri ile seyr ü sülûka dair eserinin kısaca tahliline yer verilerek bu önemli alim ve ârif tanıtılmaya çalışılmıştır.